Dampak Alih Fungsi Lahan Pertanian Menjadi Lahan Kering - Sanjesti, Winidya; Silviana, Ana (Legal Standing : Jurnal Ilmu Hukum, 2025)
Conversion of agricultural land to dry land is a crucial issue in the context of sustainable development and food security in Indonesia. This change is triggered by various factors, including urbanization, industrialization, and economic pressure on agricultural land. This study aims to analyze the impact of land conversion on environmental, social, and economic aspects. The method used is secondary data analysis from various relevant sources. The results of the study indicate that this change causes land degradation, characterized by decreased soil fertility, increased risk of erosion, and reduced biodiversity. From a social perspective, land conversion contributes to a decrease in farmers' welfare due to decreased agricultural productivity and their income. In addition, the reduction in agricultural land also has a negative impact on local food security and encourages migration to urban areas in search of better sources of livelihood. Economically, land conversion can increase land value and open up new investment opportunities, but it is often not profitable for small farmers who lose their sources of livelihood. Therefore, a sustainable land management strategy is needed through policies that are oriented towards a balance between development needs and natural resource conservation. Collaboration between the government, local communities, and the private sector is key to overcoming the negative impacts of land conversion and maintaining food security and community welfare in the future.